A polymer for electron beam photoresist and its preparation method and application

By designing polymers containing epoxy isobenzofuranyl ester structure, the shortcomings in resolution and sensitivity of existing electron beam photoresist are solved, and the photoresist performance with high resolution, high sensitivity and stable pattern lines are achieved.

CN119161524BActive Publication Date: 2025-04-08VALIANT CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411649152.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-04-08
Estimated Expiration
2044-11-19

AI Technical Summary

Technical Problem

Existing electron beam photoresist has shortcomings in resolution and sensitivity, especially the problems of low sensitivity and poor stability of graphics lines.

Method used

A polymer was designed with a structure containing an epoxy isobenzofuranyl ester structure. By leaving under the action of an acid, the sensitivity of the photoresist is improved, and the stability of the pattern lines is improved through the epoxy isobenzofuran structure with a larger steric hindrance.

Benefits of technology

The electron beam photoresist with high resolution, high sensitivity and stable graphics lines is achieved, which significantly improves the performance of the photoresist.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119161524B_ABST
    Figure CN119161524B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of photoresist technology, and in particular to a polymer for electron beam photoresist and a preparation method and application thereof, wherein the polymer has the following structural formula:; x, y, and z are respectively the mass fractions of the polymer repeating units, x is selected from 60-74%, y is selected from 25-35%, and z is selected from 1-10%, and the polymer weight average molecular weight is 2000-20000Da, and the molecular weight dispersion coefficient is 1.0-3.0. The preparation method is: monomer A, monomer B, monomer C, and free radical initiator are mixed and dissolved in an electronic grade reaction solvent to prepare a mixed solution, and then the mixed solution is added dropwise to an electronic grade reaction solvent, the reaction temperature and reaction time are controlled, and the reaction is completed, and the reaction system is added dropwise to a poor solvent to granulate to obtain the polymer. The photoresist composition prepared with the polymer has high resolution and high sensitivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a polymer used for electron beam photoresist and a preparation method and application thereof, belonging to the technical field of photoresist. Background Art

[0002] Electron-beam Lithography (EBL), as the next generation of lithography technology, is considered to be one of the most promising lithography technologies due to its high resolution and stable performance. Since the wavelength of electron rays is extremely short (wavelength 0.01~0.007nm), it can be used to prepare fine graphics with nanometer-level resolution. At present, electron beam exposure technology is mainly used to manufacture masks. With the continuous improvement of integrated circuit technology, masks for various resolution enhancement technologies are made of electron beam photoresists. Therefore. The resolution of electron beam photoresists is a key factor restricting the quality of masks. Without high-resolution electron beam photoresists, the production of high-end masks will be out of the question.

[0003] At present, polymethyl methacrylate (PMMA) is one of the main materials of electron beam photoresist, which has high resolution but low sensitivity, and requires high exposure energy and long exposure time. Modified electron beam photoresist, such as adding methyl chloroacrylate or silicone surfactant, has improved photoresist sensitivity, but the stability of graphic lines after development is poor.

[0004] In order to overcome the above defects and improve the performance of the photoresist composition, it is necessary to design a polymer for electron beam photoresist that has high resolution, high sensitivity and stable pattern. Summary of the invention

[0005] The present invention aims at the deficiencies of the prior art and provides a polymer for electron beam photoresist and a preparation method and application thereof. The photoresist composition prepared with the polymer has higher resolution, higher sensitivity and better pattern line stability.

[0006] The technical solution of the present invention to solve the above technical problem is as follows: a polymer for electron beam photoresist, the polymer has the following formula I:

[0007] Formula I;

[0008] x, y, and z are respectively the mass fractions of the polymer repeating units, x is selected from 60-74%, y is selected from 25-35%, and z is selected from 1-10%. The weight average molecular weight of the polymer is 2000-20000 Da, and the molecular weight dispersion coefficient is 1.0-3.0.

[0009] On the basis of the above technical solution, the present invention can also be improved as follows:

[0010] Preferably, in the polymer repeating unit, x is 60-70%, y is 25-30%, and z is 1-10%.

[0011] Preferably, the weight average molecular weight of the polymer is 4000-8000 Da; and the PDI is 1.0-1.8.

[0012] The present invention also discloses a preparation method for electron beam photoresist, which comprises: mixing monomer A, monomer B, monomer C and a free radical initiator, dissolving the mixture in an electronic grade reaction solvent to prepare a mixed solution, then dripping the mixed solution into the electronic grade reaction solvent, controlling the reaction temperature and reaction time, and after the reaction is completed, dripping the reaction system into water to granulate to obtain the polymer;

[0013] The monomer A is p-hydroxystyrene, the monomer B is styrene, and the monomer C is 2-methyl-2-acrylate octahydro-3-oxo-4,7-epoxyisobenzofuran-5-yl ester.

[0014] Furthermore, in terms of mass fraction, the monomer A accounts for 60-74% of the total mass of the monomers, the monomer B accounts for 25-35% of the total mass of the monomers, and the monomer C accounts for 1-10% of the total mass of the monomers.

[0015] Preferably, in terms of mass fraction, the monomer A accounts for 60-70% of the total mass of the monomers, the monomer B accounts for 25-30% of the total mass of the monomers, and the monomer C accounts for 1-10% of the total mass of the monomers.

[0016] Further, the free radical initiator is selected from any one of azobisisobutyronitrile, benzoyl peroxide, azobisisoheptanenitrile and dimethyl azobisisobutyrate. The amount of the free radical initiator is 1-20% of the total mass of the monomers (the sum of the mass of monomer A, monomer B and monomer C).

[0017] Preferably, the free radical initiator is azobisisobutyronitrile. Preferably, the amount of the free radical initiator used is 5-10% of the total weight of the monomer.

[0018] Furthermore, the electronic grade reaction solvent is selected from any one of propylene glycol methyl ether, propylene glycol methyl ether acetate, methyl isobutyl carbinol, dipropylene glycol methyl ether and isopropanol.

[0019] Preferably, the electronic grade reaction solvent is propylene glycol methyl ether.

[0020] Furthermore, the reaction temperature is 40-100° C., and the reaction time is 2-10 hours.

[0021] Preferably, the reaction temperature is 70-90° C., and the reaction time is 2-5 hours.

[0022] Furthermore, the poor solvent is at least one of methanol, ethanol and water.

[0023] The invention also discloses a photoresist composition, which comprises a polymer, a photoacid generator and an electronic grade solvent. The polymer is a polymer used for electron beam photoresist according to the invention.

[0024] The beneficial effects of the present invention are:

[0025] (1) The polymer structure involved in the present invention has an epoxy isobenzofuranyl ester structure, which requires less exposure energy to leave under the action of acid, thereby greatly improving the sensitivity of the photoresist composition.

[0026] (2) The polymer structure involved in the present invention has an epoxy isobenzofuran structure with large steric hindrance, which improves the stability of the non-exposed area of ​​the composition, reduces the solubility of the non-exposed area in the developer, increases the solubility difference between the exposed area and the non-exposed area, and has a higher resolution after imaging; and the structure has a strong polarity, which increases the interaction between the polymer and the solvent, and the pattern lines are stable and clearer after development.

[0027] (3) The polymer structure of the present invention has acid-labile hydroxyl groups, which facilitates the development and removal of the coating during the development process;

[0028] (4) The preparation method of the present invention is simple and convenient. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 For polymer Polymer B 1 H-NMR spectrum.

[0030] Figure 2 This is a scanned image of the cross-sectional morphology of the composition 3;

[0031] Figure 3 This is a scanned image of the cross-sectional morphology of composite 8. DETAILED DESCRIPTION

[0032] The specific implementation of the present invention is described in detail below. The present invention can be implemented in many other ways than those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed.

[0033] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used are only for describing specific embodiments and are not intended to limit the present invention.

[0034] The monomer A (p-hydroxystyrene), monomer B (styrene), and monomer C (2-methyl-2-acrylate octahydro-3-oxo-4,7-epoxyisobenzofuran-5-yl ester) used in the examples are all known compounds and can be purchased from the market.

[0035] 1. Polymer Preparation Example

[0036] Example 1

[0037] 16.8g of monomer A (p-hydroxystyrene), 7.0g of monomer B (styrene), 2.1g of monomer C (2-methyl-2-acrylic acid octahydro-3-oxo-4,7-epoxyisobenzofuran-5-yl ester), and 2.0g of azobisisobutyronitrile were dissolved in 80.0g of electronic grade dipropylene glycol methyl ether to prepare a mixed solution, and the mixed solution was pumped into 50.0g of electronic grade dipropylene glycol methyl ether with a metering pump, and the reaction temperature was controlled to 60-70°C, and the reaction was kept warm for 8 hours. After the reaction was completed, the system was cooled to room temperature and slowly added dropwise to 1000.0g of methanol to precipitate a white solid, which was filtered and dried to obtain polymer Polymer A 16.0 g, yield 62%, Mw = 5347 Da, PDI = 1.48 (p-hydroxystyrene: styrene: 2-methyl-2-acrylate octahydro-3-oxo-4,7-epoxyisobenzofuran-5-yl ester = 65.0%: 27.0%: 8.0% (mass fraction)).

[0038] Example 2

[0039] 16.8g of monomer A (p-hydroxystyrene), 7.0g of monomer B (styrene), 2.1g of monomer C (2-methyl-2-acrylic acid octahydro-3-oxo-4,7-epoxyisobenzofuran-5-yl ester), and 1.5g of azobisisobutyronitrile were dissolved in 100.0g of electronic grade methyl isobutyl carbinol to prepare a mixed solution, and the mixed solution was pumped into 70.0g of electronic grade methyl isobutyl carbinol with a metering pump. The reaction temperature was controlled to 80-90°C, and the reaction was kept warm for 4 hours. After the reaction was completed, the system was cooled to room temperature and slowly added dropwise to 1000.0g of isopropanol to precipitate a white solid, which was filtered and dried to obtain polymer Polymer B 16.8 g, yield 65%, Mw = 6885 Da, PDI = 1.51 (p-hydroxystyrene: styrene: 2-methyl-2-acrylate octahydro-3-oxo-4,7-epoxyisobenzofuran-5-yl ester = 65.0%: 27.0%: 8.0% (mass fraction)).

[0040] Nuclear magnetic resonance detection is: 1 H-NMR (400MHz, (CD3)2CO), δ=7.776-6.029 (CH on benzene ring), δ=5.013-2.588 (CH, CH2 on epoxyisobenzofuran), as shown in the attached Figure 1 shown.

[0041] Example 3

[0042] 16.8 g of monomer A (p-hydroxystyrene), 8.1 g of monomer B (styrene), 2.0 g of monomer C (2-methyl-2-acrylic acid octahydro-3-oxo-4,7-epoxyisobenzofuran-5-yl ester), and 1.5 g of azobisisoheptanenitrile were dissolved in 100.0 g of electronic grade propylene glycol methyl ether to prepare a mixed solution, and the mixed solution was pumped into 100.0 g of electronic grade propylene glycol methyl ether with a metering pump, and the reaction temperature was controlled to 40-50° C. The reaction was kept warm for 10 hours. After the reaction was completed, the system was cooled to room temperature and slowly added dropwise to 1000.0 g of water to precipitate a white solid, which was filtered and dried to obtain a polymer Polymer C 15.4 g, yield 57%, Mw = 6351 Da, PDI = 1.63 (p-hydroxystyrene: styrene: 2-methyl-2-acrylate octahydro-3-oxo-4,7-epoxyisobenzofuran-5-yl ester = 62.5%: 30.0%: 7.5% (mass fraction)).

[0043] Example 4

[0044] 16.8 g of monomer A (p-hydroxystyrene), 7.1 g of monomer B (styrene), 2.9 g of monomer C (2-methyl-2-acrylic acid octahydro-3-oxo-4,7-epoxyisobenzofuran-5-yl ester), and 1.5 g of dimethyl azobisisobutyrate were dissolved in 100.0 g of electronic grade propylene glycol methyl ether acetate to prepare a mixed solution, and the mixed solution was pumped into 100.0 g of electronic grade propylene glycol methyl ether acetate with a metering pump. The reaction temperature was controlled to 70-80°C, and the reaction was kept warm for 2 hours. After the reaction was completed, the system was cooled to room temperature and slowly added dropwise to 1000.0 g of methanol to precipitate a white solid, which was filtered and dried to obtain a polymer Polymer D 14.1 g, yield 52%, Mw = 7767 Da, PDI = 1.79 (p-hydroxystyrene: styrene: 2-methyl-2-acrylate octahydro-3-oxo-4,7-epoxyisobenzofuran-5-yl ester = 62.5%: 26.5%: 11.0% (mass fraction)).

[0045] Example 5

[0046] 16.8 g of monomer A (p-hydroxystyrene), 8.5 g of monomer B (styrene), 1.6 g of monomer C (2-methyl-2-acrylic acid octahydro-3-oxo-4,7-epoxyisobenzofuran-5-yl ester), and 1.5 g of benzoyl peroxide were dissolved in 100.0 g of electronic grade isopropanol to prepare a mixed solution, and the mixed solution was pumped into 50.0 g of electronic grade isopropanol with a metering pump. The reaction temperature was controlled to 50-60°C, and the reaction was kept warm for 6 hours. After the reaction was completed, the system was cooled to room temperature and slowly added dropwise to 1000.0 g of methanol to precipitate a white solid, which was filtered and dried to obtain a polymer Polymer E 14.6 g, yield 54%, Mw = 10014 Da, PDI = 1.81 (p-hydroxystyrene: styrene: 2-methyl-2-acrylate octahydro-3-oxo-4,7-epoxyisobenzofuran-5-yl ester = 62.5%: 31.5%: 6.0% (mass fraction)).

[0047] Example 6

[0048] 16.8 g of monomer A (p-hydroxystyrene), 9.7 g of monomer B (styrene), 0.4 g of monomer C (2-methyl-2-acrylic acid octahydro-3-oxo-4,7-epoxyisobenzofuran-5-yl ester), and 3.0 g of azobisisobutyronitrile were dissolved in 100.0 g of electronic grade methyl isobutyl carbinol to prepare a mixed solution, and the mixed solution was pumped into 60.0 g of electronic grade methyl isobutyl carbinol with a metering pump. The reaction temperature was controlled to 70-80°C, and the reaction was kept warm for 6 hours. After the reaction was completed, the system was cooled to room temperature and slowly added dropwise to 1000.0 g of ethanol to precipitate a white solid, which was filtered and dried to obtain a polymer Polymer F 12.6 g, yield 47%, Mw = 3137 Da, PDI = 1.31 (p-hydroxystyrene: styrene: 2-methyl-2-acrylate octahydro-3-oxo-4,7-epoxyisobenzofuran-5-yl ester = 62.5%: 36.0%: 1.5% (mass fraction)).

[0049] Example 7

[0050] 16.8g of monomer A (p-hydroxystyrene), 9.0g of monomer B (styrene), 1.1g of monomer C (2-methyl-2-acrylic acid octahydro-3-oxo-4,7-epoxyisobenzofuran-5-yl ester), and 0.5g of azobisisoheptanenitrile were dissolved in 100.0g of electronic grade propylene glycol methyl ether acetate to prepare a mixed solution, and the mixed solution was pumped into 60.0g of electronic grade propylene glycol methyl ether acetate with a metering pump, and the reaction temperature was controlled to 90-100°C, and the reaction was kept warm for 3 hours. After the reaction was completed, the system was cooled to room temperature and slowly added dropwise to 1000.0g of methanol to precipitate a white solid, which was filtered and dried to obtain a polymer Polymer G 11.9 g, yield 44%, Mw = 12527 Da, PDI = 1.95 (p-hydroxystyrene: styrene: 2-methyl-2-acrylate octahydro-3-oxo-4,7-epoxyisobenzofuran-5-yl ester = 62.5%: 33.5%: 4.0% (mass fraction)).

[0051] 2. Preparation of Photoresist Composition

[0052] The polymer prepared in the above example was mixed with a photoacid generator (4-tert-butylphenyl diphenyl sulfide nonafluorobutane sulfonate) and an electronic grade solvent propylene glycol methyl ether to prepare a photoresist composition with a certain solid content, and the known polymer Polymer X was mixed with a photoacid generator (4-tert-butylphenyl diphenyl sulfide nonafluorobutane sulfonate) and an electronic grade solvent propylene glycol methyl ether to prepare a photoresist composition with the same solid content. The formulas of each photoresist composition are shown in Table 1.

[0053] Table 1 Photoresist composition formula

[0054]

[0055] The structural formula of polymer Polymer X is as follows:

[0056] ; Among them, x:y:z=62.5%:30.0%:7.5% (mass fraction), Mw of polymer Polymer X=6291Da, PDI=1.62.

[0057] 3. Photoresist composition performance test

[0058] The photoresist composition was spin-coated on a 6-inch silicon wafer, with the rotation speed set to 0rpm / 10s, 200rpm / 2s, 0rpm / 2s, and 1500rpm / 30s. After the spin coating was completed, it was baked on a hot plate at 90°C for 1 minute, and then placed on a cold plate for cooling. Finally, electron beam exposure verification was performed at a voltage of 30kV and different exposure energy doses to obtain a clear pattern. The test equipment is as follows:

[0059] Exposure energy: electron beam exposure machine (brand / model: German Raith / Pioneer Two);

[0060] Scanning image: electron microscope (brand / model TESCAN / CLAPAGHM).

[0061] The performance test results of the photoresist composition are shown in Table 2 below.

[0062] Table 2 Photoresist composition performance test results

[0063]

[0064] As can be seen from Table 2, after the use of the photoresist polymer of the present invention (compositions 1-7), since the polymer contains epoxy isobenzofuranyl ester structure, it is easy to leave under the action of acid, which greatly reduces the exposure energy (only 60~70uC / cm 2 ), which improves the sensitivity. The composition 8 prepared by polymer Polymer X requires 150uC / cm 2 The exposure energy can form a clearer pattern.

[0065] From the line width of the formed pattern, it can be seen that after the use of the photoresist polymer of the present invention (compositions 1-7), the polymer contains a large sterically hindered epoxy isobenzofuran structure, which improves the stability of the non-exposed area of ​​the composition, reduces the solubility of the composition in the developer, increases the solubility difference between the exposed area and the non-exposed area, and the line width after imaging is narrower and the resolution is higher. However, the line width of composition 8 prepared by polymer Polymer X is 80nm, and the resolution is relatively low.

[0066] In summary, the photoresist polymer of the present invention can significantly improve the resolution and sensitivity of the composition.

[0067] Determination of photoresist cross-sectional morphology: Use scanning electron microscope to observe the cross-sectional morphology. The test results are shown in Figure 2-Figure 3 , Figure 2 This is a scanned image of composition 3. Figure 3 This is a scanned image of composition 8. Figure 2 and Figure 3 From the comparison, it can be seen that after using the photoresist polymer described in the present invention (composition 3), the morphology of the pattern is smooth and the critical size is small (40nm), which significantly improves the resolution and stability of the photoresist development pattern, while the pattern morphology of composition 8 is rough and the critical size is large (80nm). In comparison, the photoresist polymer described in the present invention has good application prospects.

[0068] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are exhaustively listed. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0069] For those skilled in the art, several modifications and improvements may be made without departing from the concept of the present invention, all of which belong to the protection scope of the present invention. The protection scope of the present invention shall be based on the attached claims.

Claims

1. A polymer for electron beam photoresist, characterized in that The polymer has the following formula I: Formula I; x, y, and z are respectively the mass fractions of the polymer repeating units, x is selected from 60-74%, y is selected from 25-35%, and z is selected from 1-10%. The weight average molecular weight of the polymer is 2000-20000 Da, and the molecular weight dispersion coefficient is 1.0-3.

0.

2. A polymer for electron beam photoresist according to claim 1, characterized in that: In the polymer repeating unit, x is 60-70%, y is 25-30%, and z is 1-10%.

3. A polymer for electron beam photoresist according to claim 1, characterized in that: The weight average molecular weight of the polymer is 4000-8000 Da; and the PDI is 1.0-1.

8.

4. A method for preparing a polymer for electron beam photoresist according to any one of claims 1 to 3, characterized in that: The preparation method comprises: mixing monomer A, monomer B, monomer C and a free radical initiator, dissolving them in an electronic grade reaction solvent to prepare a mixed solution, then dripping the mixed solution into the electronic grade reaction solvent, controlling the reaction temperature and reaction time, and after the reaction is completed, dripping the reaction system into a poor solvent to granulate to obtain the polymer; The monomer A is p-hydroxystyrene, the monomer B is styrene, and the monomer C is 2-methyl-2-acrylate octahydro-3-oxo-4,7-epoxyisobenzofuran-5-yl ester.

5. A method for preparing a polymer for electron beam photoresist according to claim 4, characterized in that: In terms of mass fraction, the monomer A accounts for 60-74% of the total mass of the monomers, the monomer B accounts for 25-35% of the total mass of the monomers, and the monomer C accounts for 1-10% of the total mass of the monomers.

6. The method for preparing a polymer for electron beam photoresist according to claim 4, characterized in that: The free radical initiator is selected from any one of azobisisobutyronitrile, benzoyl peroxide, azobisisoheptanenitrile and dimethyl azobisisobutyrate.

7. A method for preparing a polymer for electron beam photoresist according to claim 4, characterized in that: The electronic grade reaction solvent is selected from any one of propylene glycol methyl ether, propylene glycol methyl ether acetate, methyl isobutyl carbinol, dipropylene glycol methyl ether and isopropanol.

8. The method for preparing a polymer for electron beam photoresist according to claim 4, characterized in that: The reaction temperature is 40-100° C., and the reaction time is 2-10 hours.

9. The method for preparing a polymer for electron beam photoresist according to claim 4, characterized in that: The poor solvent is at least one of methanol, ethanol and water.

10. A photoresist composition, characterized in that: The photoresist composition comprises a polymer, a photoacid generator and an electronic grade solvent. The polymer is a polymer for electron beam photoresist as described in any one of claims 1 to 3, or the polymer is a polymer prepared by the method for preparing a polymer for electron beam photoresist as described in any one of claims 4 to 9.

Citation Information

Patent Citations

  • Photoresists comprising multi-amide component

    CN102591145A

  • Photoacid generator and photoresist comprising same

    CN103086934A